Electron temperature gradient drift instability in the finite beta edge plasma of a field reversed magnetic configuration - Khvesyuk, V.I.; Chirkov, A.Yu. (Вопросы атомной науки и техники, 2008)
Electromagnetic drift instabilities in the plasma of a field reversed configuration are considered with no assumption of adiabatic response of ions and/or electrons in the range of perpendicular wave number values from k┴ < 1/ρTi up to k┴ ~ 1/ρTe (ρTi and ρTe are ion and electron thermal gyroradiuses). Stabilization by finite plasma length is studied. Stabilising effect of low temperature gradients on electron mode is discussed.